PENGARUH PELATIHAN, PENGALAMAN DAN KOMPETENSI KERJA TERHADAP KINERJA PADA PT. PERMODALAN SIAK - Sheila Dwi Anggreni; Machasin -; Chairul Amsal (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2015)
The quality of human resources is determined by the extent to which the system in the field of human resources able to support and satisfy the desires of the employees and the company. In improving the performance quality of human resources and quality is necessary to increase the knowledge, skills, change in attitudes, behavior and correction of deficiencies in accordance with the required performance. This study aims to look at the effect of training, work experience and competence on the performance of employees working at the Capital Siak Company. The results of the study is that training, work experience and job competence affect the performance of the employee.Keywords: training, work experience, job competence and performance.